Respostas

A melhor resposta!
2014-05-09T18:30:56-03:00
Fórmula:
Delta=b ^{2}-4.a.c
 X=\frac{-b+- \sqrt{Delta} }{2.a}

x²+5x+6=0
a=1     b=5      c=6
/\=b²-4.a.c
/\=5²-4.1.6
/\=25-24
/\=1
x=-b+-delta
    2.a

x=-5+-1
   2.1

x=-5+-1
     2
x₁=-5+1=-2
      2

x₂=-5-1=-3
       2

x₁=-2
x₂=-3
2 5 2
2014-05-09T19:06:20-03:00
 Calcular pela FÓRMULA DE BASKARA.                                    
 x²+ 5x + 6 =0       a=1     b=5    c=6
Formula: - b +ou- 
√ b²-4ac
                      2a
-5 +ou- 
√25 - 24     x' = -5 + 1 = -2        x"= -5 - 1 = -3
             2                        2                          2